The Effect of Selling Prices on the Income of Vegetable Traders in Nipah Panjang District - Husairi, Ridwan; Abidin, Zaenal; Kuswanto (Zabags International Journal of Economy, 2025)
This study aims to examine 2 (two) variables using path analysis. The purpose of this study is to reveal the effect of selling price on the income of vegetable traders. In this study, the researcher uses quantitative research because the researcher views human behavior as predictable and social reality; objective and measurable. Therefore, the use of quantitative research with valid and reliable instruments and appropriate and appropriate statistical analysis causes the results of the research achieved not to deviate from the actual conditions. The data of this study was obtained from primary data in the form of questionnaires distributed to the population and samples. The population and sample in this study the author used sample size of 130 respondents. The sampling technique used was Accidental sampling. Based on the results of the hypothesis test, the significance value is known to be Sig value 0.000 <0.05, t count value> t table (6.947> 1.656). Thus, it can be concluded that the selling price variable has a positive and significant effect on income. Based on the results of the Determination Coefficient test, it can be concluded that the magnitude of the influence of the Selling Price Variable on income is 27.40%, while the remaining 72.60% is influenced by other factors.